DESIGNING A DIGITAL TEACHING MODULE BASED ON MATHEMATICAL COMMUNICATION IN RELATION AND FUNCTION - Setiyani Setiyani; Dian Permana Putri; Ferry Ferdianto; Sandi Hermana Fauji (Journal on Mathematics Education, 2020)
The purpose of this study is to design a digital module based on mathematical communication skills. This a development research which is carried out to determine the use of poor learning media and students’ low comprehensive skills in understanding mathematical topics associated with relations and functions. One of the solutions used to overcome this problem is by designing a digital teaching module using media. The research and development method consisting of Analysis, Design, Development, implementation, and Evaluation (ADDIE), were used to carry out this study. The results showed that the digital module is highly valid with a total expert validation of 95.1% and in the very good category. Also, the students' response to the digital module is in the very good category, with a total response criterion of 89.8%. Therefore, the designed digital module has the ability to improve students' independence in learning because its use is not limited to classrooms.